The Effectiveness of Herringbone and SQ4R as Techniques in Teaching Reading Comprehension to Students with Visual and Auditory Learning Styles - Nurhidayat, Nurhidayat (English Education Journal, 2021)
Applying the effective teaching techniques to teach reading comprehension is a must in order to overcome students’ obstacles in comprehending a texts. This study tries to analyze the effectiveness of Herringbone and SQ4R to teach reading comprehension to visual and auditory students at SMPN 2 Sedong. This study belongs to quantitative research with quasi-experimental design applying 2 x 2 factorial design with ANOVA. There are two classes chosen as samples; VIII A as the experimental class I and VIII G as the experimental class II. This study revealed that there is no interaction among techniques, reading comprehension, and learning styles in teaching reading comprehension to the visual and auditory students. Herringbone and SQ4R are effective to teach reading comprehension to students with visual and auditory learning styles. Both visual and auditory students had an equal improvement treated with herringbone and SQ4R since there is no significant difference in the improvement between visual and auditory students in reading comprehension treated by herringbone and SQ4R. Conversely, both herringbone and SQ4R had an equal effectiveness to teach reading comprehension to the visual and auditory students since there is no significant difference of effectiveness between herringbone and SQ4R to the visual and auditory students.